Towards Hardware-Intrinsic Security Foundations and Practice - Sadeghi, Ahmad-Reza.; Naccache, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Hardware-intrinsic security is a young field dealing with secure secret key storage. By generating the secret keys from the intrinsic properties of the silicon, e.g., from intrinsic Physical Unclonable Functions (PUFs), no permanent secret key storage is required anymore, and the key is only present in the device for a minimal amount of time. The field is extending to hardware-based security primitives and protocols such as block ciphers and stream ciphers entangled with the hardware, thus improving IC security. While at the application level there is a growing interest in hardware security for RFID systems and the necessary accompanying system architectures. This book brings together contributions from researchers and practitioners in academia and industry, an interdisciplinary group with backgrounds in physics, mathematics, cryptography, coding theory and processor theory. It will serve as important background material for students and practitioners, and will stimulate much further research and development.
Physically Unclonable Functions (PUFs) -- Physically Unclonable Functions: A Study on the State of the Art and Future Research Directions -- Hardware Intrinsic Security from Physically Unclonable Functions -- From Statistics to Circuits: Foundations for Future Physical Unclonable Functions -- Strong PUFs: Models, Constructions, and Security Proofs -- Hardware-based Cryptography -- Leakage Resilient Cryptography in Practice -- Memory Leakage-Resilient Encryption Based on Physically Unclonable Functions -- Hardware Attacks -- Hardware Trojan Horses -- Extracting Unknown Keys from Unknown Algorithms Encrypting Unknown Fixed Messages and Returning No Results -- Hardware-based Policy Enforcement -- License Distribution Protocols from Optical Media Fingerprints -- Anti-counterfeiting: Mixing the Physical and the Digital World -- Hardware-Security in Contactless Tokens -- Anti-counterfeiting, Untraceability and Other Security Challenges for RFID Systems: Public-Key-Based Protocols and Hardware -- Contactless Security Token Enhanced Security by Using New Hardware Features in Cryptographic-Based Security Mechanisms -- Enhancing RFID Security and Privacy by Physically Unclonable Functions -- Hardware-based Security Architectures and Applications -- Authentication of Processor Hardware Leveraging Performance Limits in Detailed Simulations and Emulations -- Signal Authentication in Trusted Satellite Navigation Receivers -- On the Limits of Hypervisor- and Virtual Machine Monitor-Based Isolation -- Efficient Secure Two-Party Computation with Untrusted Hardware Tokens (Full Version)* -- Towards Reliable Remote Healthcare Applications Using Combined Fuzzy Extraction.
Keywords: Computer science; Computer hardware; Data structures (Computer science).; Computer engineering; Computer Science; Data Structures, Cryptology and Information Theory; Computer Hardware; Electrical Engineering